1980
DOI: 10.1097/00006254-198007000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Self-Monitoring of Blood Glucose in Diabetic Pregnancy

Abstract: Summary and conclusionsAdmission to hospital is usually recommended to achieve the best possible diabetic control during pregnancy. We have used blood glucose monitoring at home to find out if patients can achieve equally good control outside hospital. Twenty-five consecutive diabetic patients were studied, of whom 20 had taken insulin before pregnancy. Six of their 14 previous pregnancies had ended in perinatal death. The 25 women performed 4247 blood glucose measurements during their pregnancies. Overall the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…No patient in our series had all measurements of capillary blood glucose below this upper limit. The percentage of results above this level was similar to a series where detailed home monitoring of blood glucose was used (Peacock et al, 1979). All our outpatient and in-patient mean blood glucose levels are at least 1 mmol/litre greater than corresponding levels in non-diabetic pregnancy (Stubbs et al, 1980) and much more variable as shown by the greater standard deviations.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…No patient in our series had all measurements of capillary blood glucose below this upper limit. The percentage of results above this level was similar to a series where detailed home monitoring of blood glucose was used (Peacock et al, 1979). All our outpatient and in-patient mean blood glucose levels are at least 1 mmol/litre greater than corresponding levels in non-diabetic pregnancy (Stubbs et al, 1980) and much more variable as shown by the greater standard deviations.…”
Section: Discussionsupporting
confidence: 80%
“…Capillary blood glucose would therefore rarely exceed 7-5 mmol/litre. For comparison in a detailed study (Peacock et al, 1979) of day-to-day monitoring of capillary blood glucose during pregnancy an overall mean level of 7.1 mmol/litre ± 26 s.d. was achieved in 25 diabetic pregnancies with satisfactory outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We too have achieved a significantly better BG regulation since we adopted the self-test regime (1,5,9,14) (Table 111) and we have had the opportunity to evaluate the effect of this on a regime which otherwise continued without further change. The BG values estimated by the laboratory at the ambulant visits decreased significantly and the number of necessary hospitalizations because of diabetic-related complications during pregnancy fell to approximately 50% without having to increase the number of ambulant check-ups.…”
Section: Discussionmentioning
confidence: 99%
“…All series published to date (Farquhar 1969;Sack 1969;Karlsson 8c Kjellmer 1972;Gabbe et al 1977;Kitzmiller et al 1978;Adashi et al 1979;Peacock et al 1979;Roversi et al 1980;Skyler et al 1980) show the dramatic reduction of infant morbidity and mortality as treatment programs for the insulin-dependent diabetic woman are established to achieve and maintain normoglycaemia.…”
mentioning
confidence: 99%